Impact of alcohol consumption on the risk of developing bladder cancer: a systematic review and meta-analysis - Vartolomei, Mihai Dorin; Iwata, Takehiro; Roth, Beat; Kimura, Shoji; Mathieu, Romain; Ferro, Matteo; Shariat, Shahrokh F; Seitz, Christian (World journal of urology, 2019)
BACKGROUND: Epidemiologic studies that investigated alcohol consumption in relation to the risk of bladder cancer (BCa) have demonstrated inconsistent results. We conducted a systematic review and meta-analysis of the literature to investigate the association of alcohol including different types of alcoholic beverages consumption with the risk of BCa. MATERIALS AND METHODS: A systematic search of Web of Science, Medline/PubMed and Cochrane library was performed in May 2018. Studies were considered eligible if they assessed the risk of BCa due to alcohol consumption (moderate or heavy dose) and different types of alcoholic beverages (moderate or heavy dose) in multivariable analysis in the general population (all genders, males or females) or compared with a control group of individuals without BCa. STUDY DESIGN: observational cohorts or case-control. RESULTS: Sixteen studies were included in this meta-analysis. Moderate and heavy alcohol consumption did not increase the risk of BCa in the entire population. Sub-group and sensitivity analyses revealed that heavy alcohol consumption increased significantly the risk of BCa in the Japanese population, RR 1.31 (95% CI 1.08-1.58, P < 0.01) in the multivariable analysis, and in males RR of 1.50 (95% CI 1.18-1.92, P < 0.01), with no significant statistical heterogeneity. Moreover, heavy consumption of spirits drinks increased the risk of BCa in males, RR 1.42 (95% CI 1.15-1.75, P < 0.01). CONCLUSION: In this meta-analysis, moderate and heavy alcohol consumption did not increase the risk of bladder cancer significantly. However, heavy consumption of alcohol might increase the risk of BCa in males and in some specific populations.
Keywords: Risk Assessment; Alcohol Drinking; pití alkoholu; mužské pohlaví; Urinary Bladder Neoplasms; Cancer risk; ženské pohlaví; hodnocení rizik; Humans; Female; Alcohol consumption; nádory močového měchýře; Bladder cancer; lidé; Male